Chemical Composition of Naftalan Oil using Different Analytical Methods - Muradov, Ali N.; Guliev, Tahir A.; Aliyeva, Jamila M.; Asadova, Gülnare A.; Çelikçi, Emine Temizel (Asian, 2025)
In this study, the chemical composition of Naftalan oil was analyzed with various techniques like gas-liquid, adsorption chromatography, liquid selective catalytic dehydrogenation and selective isomerization. The isolated components were characterized with IR spectroscopy. The information regarding the structural-group composition of the analyzed fractions, along with IR spectroscopy results, demonstrates a strong correlation and confirms the reliability of this indirect approach for quantifying naphthenic structures.
Keywords: Naftalan Oil; Naphthenic Hydrocarbons; Silica Gel; Adsorbent; Mass Spectroscopy